Pemahaman Jenis Teks Genre Bahasa Inggris Siswa Kelas VIII-A SMP IPIEMS Surabaya Melalui Media Komik - Esti Kurniasih, ; Ririn Pusparini, ; Yuri Lolita, ; Agus Widodo, (Widya Cendika, 2010)
Understanding English text types (genres) is not an easy thing. In this case, someone should be able to understand the message from the text and analyze the text structure.This paper describes the use of comic as media to help the eighth grade students of SMP IPIEMS Surabaya in understanding the English text types (genres), especially narrative text. The result of the research in general showed that (1) the students were very interested in reading comic because the pictures and the stories shown in comic were very interesting; (2) comic can motivate the students to read; and (3) comics, both comic strips and comic books are one of the learning media which are very helpful for students to understand the English text types (genres), especially narrative texts.